Assessment of Different Cooking Techniques on Residual Quantification of Ciprofloxacin and Enrofloxacin Antibiotics in Chicken. Issue 6 (7th April 2015) - Khan, Muhammad Issa; Arshad, Muhammad Sajid; Anjum, Faqir Muhammad; Riasat, Adnan; Saeed, Farhan; Hussain, Shahzad; Sohaib, Muhammad
Abstract: The present research project was intended to assess the antibiotics residues in poultry meat and to explore the impacts of different cooking methods on antibiotic residues in broiler meat. Three dose levels (10, 20 and 40 mg/kg body weight) of antibiotics were administered to the broilers. The antibiotics were administered for 5 consecutive days at the age of 25 days. The birds were slaughtered after 4 days of administration of antibiotics. The residual concentrations of the drugs were highest in treatments T3 and T6 which contain maximum doses of ciprofloxacin and enrofloxacin, respectively. The maximum depletion of ciprofloxacin occurred after boiling and frying method of cooking followed by that of grilling and steaming of broiler meat. It is concluded that the residual concentrations of both antibiotics were found to be highest in all meat samples which exceeded the residual limit (0.3 ppm). Practical Applications: The key to growth is a continuous evaluation and modification of the product to match consumer expectations and regulations requirements. Currently, there are many apparent benefits that result from this research because it explains impact of different cooking methods on the antibiotic residues in poultry meat and meat products.